Other Sexuality: A Study of the Discourse of LGBTQ Sexuality and the PLUSH Community in the Special Region of Yogyakarta - Almira, Raissa; Pinem, Milda Longgeita BR. (Devotion : Journal of Research and Community Service, 2024)
The purpose of this research was to find out the experiences of informants with regard to their sexuality and to look at the role of PLUSH in the discourse of 'non-normative' sexuality in Indonesia, more specifically Yogyakarta. This research method is a qualitative research with a'mini' approach to discourse analysis by Foucault, research informants, data collection techniques (interviews, literature studies, documentation, and other media sources), data presentation, and triangulation. The data used came from primary data, namely interviews with the five informants (Bhista (30), Shamil (37), Nakula (35), Abimanyu (23) and Rangga (26), as well as secondary data from reliable sources (documentation from the media, literature, and others). The results of this study are as follows: (1) a world dominated by heteronomous concepts, where general discourse tends to corner non-binary sexuality, as experienced by members of the PLUSH, an LGBTQ advocacy organization. (2) The research contributes to the fields of community empowerment, social movements, LGBTQ studies, and social policy by providing a platform for marginalized voices and documenting new social movements. (3) The research is based on the theory of panopticon prison theory, which is used to describe the experience of the informants in exploring and fighting for their sexual identity in the context of a dominating discourse. It is hoped that further research can involve informants from various sexual orientations such as asexual and bisexual, to provide a more comprehensive picture of non-heteronormal sexuality discourse.